Leptospirosis (2006)
¿Qué es la leptospirosis?/Epidemiología de la leptospirosis/Manifestaciones clínicas/Diagnóstico de laboratorio/Tratamiento/Prevención/Preguntas/¿Cuándo se debe consultar al médico?/¿Cuándo se debe hospitalizar un paciente con leptospirosis?